Curandeiras e bruxas: práticas de feitiçaria e a subversão da ordem social no estado do Grão-Pará (1763-1769) - Suris, Andreia (Universidade do Vale do Rio dos Sinos, 2024)
This research aims to investigate the witchcraft practices (healing, divination, and love enchantments) involving women in 18th century Grão-Pará. It examines whether these practices can be understood as forms of resistance and subversion against the normative and patriarchal social order in which these women lived. The primary historical source used is the "Livro de Denunciações e Confissões” from the last visitation of the Court of the Inquisition in Portuguese America, which took place in the Grão-Pará captaincy (1763-1769), focusing on the denunciations and confessions of magical-religious practices. Additionally, the research includes two case studies that stood out: Sabina, an indigenous woman, and Luduvina Ferreira, two renowned healers in Pará society at the time of the visitation, both of whom were prosecuted by the Portuguese Inquisition.
Keywords: Mulheres; Feitiçaria; Visitação do Santo Ofício; Grão-Pará e Maranhão; Inquisição; Women; Witchcraft; Court of the Inquisition; Grão-Pará and Maranhão; Inquisition; ACCNPQ::Ciências Humanas::História